2016
DOI: 10.1080/0309877x.2015.1117598
|View full text |Cite
|
Sign up to set email alerts
|

Stress among UK academics: identifying who copes best

Abstract: This paper examined the levels of stress and coping strategies among UK academics.Adopting a positive psychology approach, the influence of the character strengths of hope, optimism, gratitude and self-efficacy, on stress, subjective well-being (SWB), and mental health (GHQ) was examined in 216 academics in a UK university. The study explored the relationship between coping styles and work-coping variables of sense of coherence and work locus of control and stress. No significant differences on the stress, wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 63 publications
1
37
0
Order By: Relevance
“…Studies reviewed reveal that intense job demands tend to trigger high levels of stress (Boyd et al, 2011;Darabi et al, 2017b;Simons et al, 2019) and burnout (Zábrodská et al, 2018). However, in an interesting study, Bell et al (2012) found that usual job demands and pressure made no difference to well-being.…”
Section: Resultsmentioning
confidence: 99%
“…Studies reviewed reveal that intense job demands tend to trigger high levels of stress (Boyd et al, 2011;Darabi et al, 2017b;Simons et al, 2019) and burnout (Zábrodská et al, 2018). However, in an interesting study, Bell et al (2012) found that usual job demands and pressure made no difference to well-being.…”
Section: Resultsmentioning
confidence: 99%
“…Individuals can employ inward or outward coping behaviours. Inward strategies could include acceptance and reframing (Darabi, Macaskill & Reidy, 2017). Outward tactics include activation strategies such as pleasure and attainment (Mitchell, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It originated with the work of Antonovsky (1987). As explained by Kinman (2008) and Darabi et al (2017), an employee's sense of coherence relates to the comprehensibility, manageability and meaningfulness of their work tasks. If these generate a strong sense of coherence, then the person is able to cope more effectively with stress and maintain their well-being.…”
Section: Academic Analysis and Advocacymentioning
confidence: 99%